P systems with membrane creation and rule input - Miguel A. Gutiérrez-Naranjo; Mario J. Pérez-Jiménez (Fénix Editora, 2005)
When a uniform family of recognizer P systems is designed to solve a problem, the data of a concrete instance of the problem is usually provided via a multiset which is placed in the so-called input membrane. In this paper we present a new definition for recognizer P systems with rule input, where the data of the instance is provided via a new set of rules. We also discuss a new semantic for P systems with membrane creation and as example, a uniform family for recognizer P systems with rule input which solves the Subset Sum problem is provided.